Management of a Rare Complication of Epidural Analgesia in an Obese Laterally Positioned Parturient: Catheter Entrapment Next to the Inferior Vena Cava. Issue 6 (1st November 2015) - Amir, Alexander; Lash, Vynka; Moore, Albert; Rao, Pramod; Torres, Carlos; Kaufman, Ian
Abstract : Abstract: Intravascular, subdural, intrathecal, and subcutaneous placement of epidural catheters are known complications and common causes of anesthesia and analgesia failure. Because the epidural space is located near the retroperitoneum and catheters are placed blindly, it is possible that misplacement could involve other structures, including the inferior vena cava, the aorta, and the lumbar plexus. We report a case of an obese laterally positioned parturient who presented with an epidural catheter lodged in the retroperitoneum. The catheter provided inadequate analgesia for labor, and postpartum computed tomography revealed it to be located in the retroperitoneal space just adjacent to the inferior vena cava. Conventional removal techniques were unsuccessful, and the catheter was finally removed after insertion of a guide wire under fluoroscopy. We conclude that obesity and lateral positioning are factors that increase the risk of epidural catheter misplacement, and a large distance from skin to loss of resistance is a potential sign of misplacement. We recommend ultrasound imaging to aid in the insertion of epidural catheters in high-risk patients.